Integrated solution for 802.1x in wired network - Gonçalo, Rui (2022)
Most organizations don’t have mechanisms to enable user monitoring and authentication over wired networks. The goal was to analyze alternatives to implement authentication and monitoring connections to enable to detect and prevent some threats and problems on user computers that can impact the normal operation of the organization. The proposed solution was divided in three components. First a machine running pfSense for network routing and services that also enabled to sent NAT translating info to remote system logs. Then followed the use of 802.11x protocol, to authenticate and authorize users, forcing any device connected to the switch to authenticate. This request is made to a RADIUS server (running on the pfSense) using remote LDAP server with the user account information. Without proper credentials equipment can’t access the network. The final component was the implementation of a log event manager, using Graylog that makes easier to visualize and filter the information, enabling the use of an API to custom query, especially one created by us, which for a given timestamp and external IP and port identify the user. This solution allows organizations to control who can access the network and when detecting incident enabled to identify the owner of the problematic equipment.